2019
DOI: 10.1016/j.neuron.2019.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Coupling in the Dentate Gyrus Regulates Adult Hippocampal Neurogenesis

Abstract: Highlights d Hippocampus-engaged exploration induces functional hyperemia in the dentate gyrus d Functional hyperemia is critical to exploration-induced hippocampal neurogenesis d Parvalbumin-expressing neurons increase blood flow via nitric-oxide signaling d Functional hyperemia elevates IGF-1 pathway activity in the dentate gyrus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 60 publications
1
44
0
1
Order By: Relevance
“…We next recorded neuronal activity of the primary auditory cortex from well-trained mice using in vivo Ca 2+ imaging. We expressed GCaMP6f, an ultrasensitive Ca 2+ sensor protein [7], in the primary auditory cortex by the stereotaxic injection of adeno-associated virus (AAV) and then implanted a prism lens above the injection site for Ca 2+ imaging using miniaturized fluorescence microscopy, as described previously [12, 24] (Fig. 2a & b).…”
Section: Resultsmentioning
confidence: 99%
“…We next recorded neuronal activity of the primary auditory cortex from well-trained mice using in vivo Ca 2+ imaging. We expressed GCaMP6f, an ultrasensitive Ca 2+ sensor protein [7], in the primary auditory cortex by the stereotaxic injection of adeno-associated virus (AAV) and then implanted a prism lens above the injection site for Ca 2+ imaging using miniaturized fluorescence microscopy, as described previously [12, 24] (Fig. 2a & b).…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced VEGF/VEGFR signaling may contribute to attenuating cognitive deficits after epileptic seizures by promoting adult neurogenesis in the dentate gyrus (Rosenstein et al, 2010;Han et al, 2017). The relationship between adult neurogenesis and the NVU has been studied (Goldman and Chen, 2011), and a recent study reported that microvascular hemodynamics modulate adult neurogenesis (Shen et al, 2019). Furthermore, VEGF administration suppressed neuronal loss in the hippocampal CA1 region 24 h but not one month after pilocarpine-induced SE in rats (Nicoletti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The authors proved that this effect is mediated by parvalbumin-expressing neurons which increase blood flow via nitric-oxide signaling. This increase in the microvascular hemodynamics enhances IGF-1 signaling promoting the newborn cell survival ( Shen et al, 2019 ).…”
Section: Cellular Components Of the Hippocampal Neurogenic Nichementioning
confidence: 99%